The time divide in cross-national perspective: the work week, gender and education in 17 countries - Frase, Peter; Gornick, Janet C. (Luxembourg, 2009)
"Prior empirical studies have found that American workers report longer hours than workers in other highly industrialized countries, and that the highly educated report the longest hours relative to other educational levels. This paper analyzes disparities in working hours by gender and education levels in 17 high- and middle-income countries in order to assess whether this nding holds cross-nationally. In contrast to many prior studies of working time, we use a measure of weekly rather than annual hours worked, which we argue provides a better window on the discretionary time available to individuals and households. We nd that: 1) average weekly male hours in the United States do not appear exceptional, with averages exceeding 40 hours per week in both the U.S. and most western European countries; 2) U.S. women work longer hours than women in most other rich countries; 3) the within-country dierence in average hours by education is not uniform, with higher-income countries more likely to show the U.S. pattern, and middle-income countries showing the reverse pattern, with the less educated reporting longer hours. We conclude by assessing some possible macro-level explanations for this variation, including per capita GDP, tax rates, unionization, and earnings inequality."